KONSEP PENDIDIKAN DALAM PEMIKIRAN IBNU KHALDUN - Hasanah; Maulida maulida; Irma Aryani; Rini Susiani; Sri Ramha Yanda (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
This study aims to look at the thoughts of Ibn Khaldun in education. Ibn Khaldun is a prominent Islamic scientist who has a great influence in science who is better known as an expert in history and sociology as well as in the world of education. The results of the study found that Ibn Khaldun views education as having a goal in developing the ability to think, good behavior, and also human attitudes in the learning process, then this process will create expertise, and bring it to maturity in socializing oneself as a member of society and will be beneficial. in the social system. With the concept of education, Ibn Khaldun views that education is a conscious effort in developing all the potential possessed by humans. The methods applied in learning according to Ibn Khaldun vary widely such as the phasing method, the method of repetition of material, the method of spreading love, the method of observing the maturity of the age of students in studying the Qur'an, and there is also a field trip method that makes it easy for participants to connect directly between theory and practice in the field. The role of religion is very important in human life, especially for people who are studying with any type of knowledge, then with science humans will have a valuable life, and with religion human life will be more perfect and meaningful.